2022
DOI: 10.1001/jama.2022.7424
|View full text |Cite
|
Sign up to set email alerts
|

Resident Physician Wellness Postpandemic

Abstract: This Viewpoint highlights the risk of burnout and its effects on resident physicians treating patients during the stressful COVID-19 pandemic and summarizes strategies for preventing burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Related to having less experience, residents have little control over their work life/scheduling, and their clinical decisions must be looked over by more experienced practitioners, leading to feelings of depersonalization and emotional exhaustion. 1,5 These feelings are present across all specialties. 6 Vijay et al conducted a study of residents near the beginning of the pandemic and found that greater than 50% of residents had symptoms of emotional exhaustion, and only 42.9% felt valued by their institution.…”
Section: Stressorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Related to having less experience, residents have little control over their work life/scheduling, and their clinical decisions must be looked over by more experienced practitioners, leading to feelings of depersonalization and emotional exhaustion. 1,5 These feelings are present across all specialties. 6 Vijay et al conducted a study of residents near the beginning of the pandemic and found that greater than 50% of residents had symptoms of emotional exhaustion, and only 42.9% felt valued by their institution.…”
Section: Stressorsmentioning
confidence: 99%
“… 6 Vijay et al conducted a study of residents near the beginning of the pandemic and found that greater than 50% of residents had symptoms of emotional exhaustion, and only 42.9% felt valued by their institution. 1 Outside of work, Natsuhara et al described that the need to wear a mask leads to depersonalization because it hides emotions and the identities of practitioners, changing human interaction. 5 …”
Section: Stressorsmentioning
confidence: 99%
See 3 more Smart Citations